The remarkable life of the skin : An intimate journey across our surface - Lyman, Monty (Bantam Press, 2019)
How does our diet affect our skin? What makes the skin age? And why can't we tickle ourselves? Providing a cover for our delicate and intricate bodies, the skin is our largest and fastest growing organ. We see it, touch it and live in it every day. It's a habitat for a mesmerizingly complex world of micro-organisms and physical functions that are vital to our health and our survival. It's also one of the first things people see about us and is crucial to our sense of identity. And yet how much do we really know about it? Through the lenses of science, sociology and history, Dr Monty Lyman leads us on a journey across our most underrated and unexplored organ and reveals how the skin is far stranger and more complex than you've ever imagined.